UJI AKTIVITAS JAMU GENDONG KUNYIT ASAM (Curcuma domestica Val.; Tamarindus indica L.) SEBAGAI ANTIDIABETES PADA TIKUS YANG DIINDUKSI STREPTOZOTOCIN - Mohamad Andrie; Wintari Taurina; Rizqa Ayunda (Majalah Obat Tradisional, 2014)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia. “Jamu gendong kunyit asam” (Curcuma domestica Val.; Tamarindus indica L.) is a traditional medicine that has antioxidant activity which can contribute to diabetic because of the phenolic content. This aim of this study is to determine the effect of “jamu gendong kunyit asam” on lowering blood glucose levels and repairing damage of the islet cells. 25 male wistar rats (Rattus norvegicus) were divided into five groups. Group I as a normal group without any treatment, group II, III, IV and V were induced with streptozotocin (7mg/ 200gBB) then treated with  CMC 1%, glibenclamide (0.27mg / 200gBB), “jamu gendong kunyit asam” 1.90mL/ 200gBB and 3.80mL/ 200gBB. The treatment was done for 28 days. Glucometer was used to measure the gloucose blood level on day 4, 8, 12, 16, 20, 24 and 28. The damages on the islet cells were examined under the microscope on the histology sample of pancreas prepared with Hematoxyllin eosin stain. Datas were analyzed statistically with One Way Anova test, T-Test, and the Kruskal-Wallis test using SPSS 17.0 for Windows. Results showed there is a significant difference (p> 0.05) in blood glucose levels and damage to the islets of Langerhans of the pancreas between the glibenclamide group and treatment of “jamu gendong kunyit asam”. From the research it can be concluded that the “jamu gendong kunyit asam” have antidiabetic activity which is  showed by a decrease in blood glucose levels and an improvement of pancreatic islets of Langerhans in streptozotocin-induced diabetic rats with an effective dose of 1.90mL/ 200gBB.